Performance based Analysis of Load Balancing Techniques and Algorithms in the Public Cloud Computing Environment - Dr. Anand Kr. Shukla,Dr. Amit Jain (International Journal of Advanced Science and Technology, 2020)
Nowadays almost all service providers IT companies are using cloud computing technologies; they are using clouds in place of servers for storage as well as for providing their services to the users. Clouds are becoming the solutions for several problems; users are getting the resources in several manners like they can access software, hardware and infrastructure as services because of clouds only. As because of such important role, there are lot of technologies methodologies and algorithms are involve which helps clouds for smoothly working with proper efficiency in load distribution and service providing. But as per the study and analysis that is also observed that accuracy rate are still need to improved specially in the distributions of loads among the clouds based servers. In this paper author has proposed some techniques for the improvement in efficiency in the load distributions